A systematic review of the outcomes reported in cardiac arrest clinical trials: The need for a core outcome set. (March 2015) - Whitehead, L.; Perkins, G.D.; Clarey, A.; Haywood, K.L.
Abstract: Background: There is a limited guidance for outcome reporting for cardiac arrest trials. This review was conducted to explore the degree of variation and identify trends in outcome reporting. Methods: Randomised controlled trials enrolling patients with cardiac arrest (2002–2012) were identified by applying a search strategy to four databases. Titles, abstracts and short-listed studies were independently assessed for eligibility. Data on the primary and secondary outcome measures, details of outcome reporting and reproducibility were extracted. Results: 61 studies matched the inclusion criteria. There was wide variation in the focus, method and timing of assessment. Outcomes most commonly reported across studies were: survival (85.2%), activities (52.5%), body structure or function (41.0%), and processes of care (26.2%). Over 160 individual outcomes were reported including 39 different reports of survival measures of which 11 were measurements of ROSC (return of spontaneous circulation). Twenty different assessments of activity limitation were reported; only one was patient-reported. Many assessments were poorly defined or non-reproducible. The majority of outcomes were assessed up to hospital discharge (89.3%). There was no one outcome measure that was assessed across all trials. Conclusions: Outcome reporting in cardiac arrest RCTs lacks consistency and transparency. Guidance for improved outcome reporting is urgently required to reduce this heterogeneity in reporting, improve the quality of assessment in clinical trials, and to support the synthesis of trial data. The results highlight the importance of working towards a core outcome set for cardiac arrest clinical trials to maximise the utility of future research.